2022
DOI: 10.1111/ejn.15816
|View full text |Cite
|
Sign up to set email alerts
|

Confirming an antiphasic bicyclic pattern of forward entrainment in signal detection: A reanalysis of Sun et al. (2021)

Abstract: as well as Monte Carlo simulations. There are 7 primary figures and 4 supplemental figures. DATA FILES:The data file from Sun et al., named "sundata.mat" contains 41400 rows by 8 columns. This data file has been cropped to include only those columns relevant to the current analysis. Each subject's data is contained in 1800 rows (1800x23=41400).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…See text for details Hickok, 2021). Similar intersubject variability has also been reported by Jones et al (2002), Lawrence et al (2014), Bauer et al (2015, and Sun et al (2021), where a proportion of their subjects show forward entrainment and a proportion do not under the same experimental conditions (see also Saberi & Hickok, 2022a). These proportions vary widely across studies.…”
Section: Effects Of Experience and Intersubject Variabilitysupporting
confidence: 66%
See 3 more Smart Citations
“…See text for details Hickok, 2021). Similar intersubject variability has also been reported by Jones et al (2002), Lawrence et al (2014), Bauer et al (2015, and Sun et al (2021), where a proportion of their subjects show forward entrainment and a proportion do not under the same experimental conditions (see also Saberi & Hickok, 2022a). These proportions vary widely across studies.…”
Section: Effects Of Experience and Intersubject Variabilitysupporting
confidence: 66%
“…Subject-specific phase dependency has been reported for simultaneous entrainment (Henry & Obleser 2012), and a phase drift in the dips and peaks of performance has been reported by Farahbod et al (2020) in a forward entrainment task as a function of the entraining modulation rate. Variable starting-phase effects have also been reported by Sun et al (2021) for a proportion (35%) of their subjects who showed forward entrainment (see also a critique of Sun et al's findings by Saberi & Hickok, 2022a).…”
Section: Effects Of Experience and Intersubject Variabilitymentioning
confidence: 78%
See 2 more Smart Citations
“…More recent studies have investigated how the informational content of masking sequences in multisource settings adversely affect the processing of temporally nonoverlapping signals. Processing of these types of temporal sequences goes beyond passive coding of informational content and may have critical predictive value for processing of impending (future) speech segments and other periodic or quasiperiodic natural sounds as demonstrated in neural and psychophysical forward entrainment [75][76][77][78][79][80]. The current study shows that brain-lesioned individuals are particularly vulnerable to interfering sequences of sounds that mask the pattern of temporal information in a target sound.…”
Section: Discussionmentioning
confidence: 91%